2011
DOI: 10.1103/physreva.84.023413
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic single-atom excitation via adiabatic passage and Rydberg blockade

Abstract: We propose to use adiabatic rapid passage with a chirped laser pulse in the strong dipole blockade regime to deterministically excite only one Rydberg atom from randomly loaded optical dipole traps or optical lattices. The chirped laser excitation is shown to be insensitive to the random number N of the atoms in the traps. Our method overcomes the problem of the √ N dependence of the collective Rabi frequency, which was the main obstacle for deterministic single-atom excitation in the ensembles with unknown N,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 35 publications
2
65
0
1
Order By: Relevance
“…To prepare the system in this crystalline phase, a dynamical approach has been suggested that adiabatically connects the ground state containing no Rydberg excitations with the targeted crystalline state. At the heart of this dynamical crystallization technique is the coherent control of the many-body system [2][3][4][14][15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare the system in this crystalline phase, a dynamical approach has been suggested that adiabatically connects the ground state containing no Rydberg excitations with the targeted crystalline state. At the heart of this dynamical crystallization technique is the coherent control of the many-body system [2][3][4][14][15][16][17].…”
mentioning
confidence: 99%
“…To prepare the system in this crystalline phase, a dynamical approach has been suggested that adiabatically connects the ground state containing no Rydberg excitations with the targeted crystalline state. At the heart of this dynamical crystallization technique is the coherent control of the many-body system [2][3][4][14][15][16][17].Previous experiments showed direct or indirect evidence for correlations caused by the long-range interac- * Electronic address: peter.schauss@mpq.mpg.de tions in Rydberg many-body systems, such as a universal scaling of the Rydberg excitation number [18], subPoissonian counting statistics [17,19,20], photon correlations [21,22], characteristic exciton dynamics [23] or spatial ordering of the excitations [24][25][26]. However, all measurements have predominantly probed features of excited many-body states that -next to the ground stateare also strongly influenced by the dramatically enhanced interaction scales.…”
mentioning
confidence: 99%
“…It is a bit special that except the three Rabi frequencies Ω gm , Ω me , and Ω er , the detunings ∆ e and ∆ r should also change over time to meet the quasi-dark condition (5). This could be achieved through coupling state |m and state |e , state |e and state |r by two frequency-chirped optical pulses, the technology of which has been widely investigated in the theory and the experiment of atomic and molecular state control [40][41][42][43][44][45]. The time sequence of pulses and the time dependence of detunings for our chirped multiphoton adiabatic passage are displayed in Fig.…”
Section: Chirped Multi-photon Adiabatic Passagementioning
confidence: 99%
“…[44]. The frequency (detuning) ∆ las (t) of the effective laser coupling between | g and | s is adjusted from negative detuning to positive detuning in the course of a Gaussian envelope pulse for Ω las (t).…”
Section: A Excitation Of Blockade Statesmentioning
confidence: 99%